2021
DOI: 10.1002/mds.28826
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glutathione and Prodromal Parkinson's Disease Probability

Abstract: Background A decrease in glutathione (GSH) levels is considered one of the earliest biochemical changes in Parkinson's disease (PD). Objective The authors explored the potential role of plasma GSH as a risk/susceptibility biomarker for prodromal PD (pPD) by examining its longitudinal associations with pPD probability trajectories. Methods A total of 405 community‐dwelling participants (median age [interquartile range] = 73.2 [7.41] years) without clinical features of parkinsonism were followed for a mean (stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The lower baseline plasma GSH levels were reported to be associated with an increased risk of developing neurodegenerative diseases, such as AD and PD. 244,245 In addition, the body's antioxidant system also faces the loss of enzyme activity in GSH synthesis, which is crucial to the antioxidant response. As an important antioxidant enzyme, GPX4 conducts its biological activity by converting two molecules of GSH to oxidized glutathione (GSSG) along with reducing phospholipid hydroperoxides (PL-OOH) to phospholipid hydroxides (PL-OH), to prevent the accumulation of lipid peroxides, which is toxic.…”
Section: Reduction Of Gsh: the Collapse Of Antioxidant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower baseline plasma GSH levels were reported to be associated with an increased risk of developing neurodegenerative diseases, such as AD and PD. 244,245 In addition, the body's antioxidant system also faces the loss of enzyme activity in GSH synthesis, which is crucial to the antioxidant response. As an important antioxidant enzyme, GPX4 conducts its biological activity by converting two molecules of GSH to oxidized glutathione (GSSG) along with reducing phospholipid hydroperoxides (PL-OOH) to phospholipid hydroxides (PL-OH), to prevent the accumulation of lipid peroxides, which is toxic.…”
Section: Reduction Of Gsh: the Collapse Of Antioxidant Systemmentioning
confidence: 99%
“…Therefore, normal GSH content is essential for the maintenance of the cellular antioxidant system. The lower baseline plasma GSH levels were reported to be associated with an increased risk of developing neurodegenerative diseases, such as AD and PD 244,245 …”
Section: Ferroptosis: the Ending Of Iron Overloadmentioning
confidence: 99%
“…It is an important antioxidant that traps free radicals and thus effectively protects cells from oxidative stress [57] . Besides, changes in GSH levels have been linked to a variety of human diseases, including liver damage, [58] lung disease, [59] Parkinson's disease, [60] AIDS, [61] and cancer [62] . Thus, monitoring the levels of GSH in cells and in vivo is important.…”
Section: Biomedical Application Of Organic Afterglow Nanoparticlesmentioning
confidence: 99%
“…A blood-based DNA methylation study showed cg06690548 hypermethylation on chromosome 4 in patients with PD, is associated with downregulation of the SLC7A11 gene that codes for xCT (Vallerga and others 2020). Reduction in plasma glutathione is an early indicator of PD (Charisis and others 2022). Moreover, the 6-OHDA model of PD, in vivo and in vitro, showed GSH depletion and iron accumulation and increased lipid peroxidation (MDA) (Sun and others 2020).…”
Section: Ferroptosis In Neurological Conditionsmentioning
confidence: 99%